Building Resilience for Uncertain Water Futures - Gober, Patricia (Springer International Publishing, 2018)
This book describes the existential threats facing the global water systems from population growth and economic development, unsustainable use, environmental change, and weak and fragmented governance. It argues that 'business-as-usual' water science and management cannot solve global water problems because today's water systems are increasingly complex and face uncertain future conditions. Instead, a more holistic, strategic, agile and publically engaged process of water decision making is needed. Building Resilience for Uncertain Water Futures emphasises the importance of adaptation through a series of case studies of cities, regions, and communities that have experimented with anticipatory policy-making, scenario development, and public engagement. By shifting perspective from an emphasis on management to one of adaptation, the book emphasizes the capacity to manage uncertainties, the need for cross-sector coordination, and mechanisms for engaging stakeholder with differing goals and conflict resolution. This book will be a useful resource for students and academics seeking a better understanding of sustainable water use, water policy and water resources management. .